Self-Assembled Naphthylidene-Containing Schiff Base Anchored Polystyrene Nanocomposites Targeted for Selective Cu(II) Ion Removal from Wastewater - Liu, Yamei (ACS Omega, 2019)
[Image: see text] Self-assembled composite adsorbents that combine the controllability of self-assembly with a mild operation process are promising for removal of heavy metal ions in wastewater. The design and preparation of functionalized composite adsorbent materials with multiple-site adsorption ability remain the most attractive in effectively removing heavy metal ions. Inspired by the macroporous structure of charged polystyrene (PS) resin and chelation of Schiff bases with heavy metal ions, smart composite adsorbents are constructed based on the combination and synergistic effect of multiple hydrophobic, π–π stacking, and electrostatic noncovalent interactions between polystyrene resin and naphthylidene-containing Schiff base (NSB). The resulting hybrid nanomaterials (PS-NSB) have uniform porous structures and well-defined and multiple target sites. These properties promote diffusion of the target ion, increase the binding site, and enhance the removal efficacy. This study offers a new strategy to harness a self-assembled Schiff base with integrated flexibility and multifunctions to enhance target metal ion specific binding and removal effects, highlighting opportunities to develop smart composite adsorbents.